Comprehensive Toughness Dataset of Nuclear Reactor Structural Materials using Charpy V-Notch Impact Testing - Isshu Lee; John W. Merickel; Yugandhar Kasala Sreenivasulu; Fei Xu; Yalei Tang; Joshua E. Rittenhouse; Aleksandar Vakanski; Rongjie Song (Scientific Data)
Abstract Reactor pressure vessel (RPV) steels are critical for maintaining the structural integrity and safety of nuclear reactors, designed to endure extreme conditions over prolonged operational lifetimes. Evaluating the mechanical properties of RPV steels frequently involves tests with sub-sized specimens, due to size constraints associated with irradiated materials. However, the reduced specimen dimensions introduce a size effect that alters material behavior and requires correlating the test results to full-sized specimens. Although numerous correlation methods have been previously proposed, they are typically applicable to specific test conditions. To address these challenges, this study introduces a public dataset of 4,961 Charpy impact test records for RPV steels. The dataset was compiled through a comprehensive literature review and incorporates data from 109 peer-reviewed publications. It provides detailed information on material composition, manufacturing treatments, specimen dimensions, testing conditions, and test results. The primary objective of the dataset is to advance the understanding of specimen size effect in Charpy impact testing, and support studies for validating existing methods and developing data-driven approaches for test results correlation.